Programmed death 1 and its ligands do not limit experimental foreign antigen‐induced immune complex glomerulonephritis. (December 2015) - Ooi, Joshua D; Li, Ming; Kourkoutzelos, Katerina; Yagita, Hideo; Azuma, Miyuki; Holdsworth, Stephen R; Kitching, A Richard
Abstract: Aim: Interactions between the co‐stimulatory molecule programmed death 1 (PD‐1) and its ligands, PD‐L1 and PD‐L2, constrain T‐cell responses and help maintain peripheral tolerance. Glomerulonephritis can result from a variety of antigens, both self and foreign, and from humoural and cellular effector responses. These studies aimed to define the role of PD1 and its ligands in circulating immune complex glomerulonephritis induced by immunity to a foreign antigen. Methods: Immune complex glomerulonephritis was initiated by injecting BALB/c mice with horse spleen apoferritin intraperitoneally daily for 14 days. Inhibitory anti‐mouse PD‐1, anti‐PD‐L1 or anti‐PD‐L2 antibodies were administered every other day. Renal disease and immune responses were studied. Results: Daily injection of horse spleen apoferritin‐induced proliferative immune complex glomerulonephritis in control antibody‐treated mice, but inhibiting PD‐1 did not augment renal injury. Specifically, blocking PD‐1 did not increase serum antigen‐specific antibodies or increase glomerular immunoglobulin G deposition, the hallmark of injury in this model. Furthermore, C3 deposition was unaffected and glomerular macrophages were reduced after anti‐PD‐1 antibodies. However, anti‐PD‐1 administration did increase splenocyte proliferation and cytokine production including interferon‐γ, interleukin (IL)‐4, and IL‐17, but not IL‐10. Neutralizing either PD‐L1 or PD‐L2 alone did not result in major alterations in renal injury. Conclusion: The endogenous PD‐1/PD‐L pathway does not limit acute experimental foreign antigen‐induced circulating immune complex glomerulonephritis. Summary at a Glance: This study shows that blockade of programmed death 1 and its ligands did not augment the renal injury in non‐autoimmune circulating immune complex glomerulonephritis, in contrast to autoimmune‐mediated disease.